2017
DOI: 10.3233/cbm-161576
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic differentiation and cell calcification of adamantinomatous craniopharyngioma induced by bone morphogenetic protein-2

Abstract: Our study demonstrated for the first time that ACP cells could differentiate into an osteoblastic lineage via induction by Bmp2. The mechanism of ACP calcification likely involves osteoblastic differentiation modulated by Bmp2. Further studies targeting Bmp2 cascades could result in novel therapeutic interventions for recurrent ACP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…1 A-D) [ 1 , 2 ]. CP calcification mostly occurs in adamantinomatous craniopharyngioma (ACP), while calcification is rarely seen in squamous papillary craniopharyngioma (SPCP) [ 3 ]. Histologically, cell pattern of ACP is different from SPCP (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 A-D) [ 1 , 2 ]. CP calcification mostly occurs in adamantinomatous craniopharyngioma (ACP), while calcification is rarely seen in squamous papillary craniopharyngioma (SPCP) [ 3 ]. Histologically, cell pattern of ACP is different from SPCP (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 E, F ). This difference may be explained by the theory that ACP originates from odontogenic rests associated with remnants of Rathke’s pouch, while SPCP develops from buccal mucosa rests [ 3 , 4 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the factors, bone morphogenetic proteins (BMPs) have been proven to facilitate bone healing without bone tissue transfer (5). Studies have indicated that BMP-2, a protein of BMP family, has important roles in bone generation-associated processes, including osteoblastic differentiation (6), the healing process of segmental bone defects (7) and the capacity of bone marrow stromal cells (BMSCs) to undergo osteogenesis (8), and has been approved by the Food and Drug Administration of the USA for clinical use in the orthopedic and dental fields (9). However, large amounts of BMP-2 are required to achieve clinically significant bone regeneration and BMP-2 is easily inactivated by dilution or interaction with enzymes in the blood if applied alone by intravenous injection (1012).…”
Section: Introductionmentioning
confidence: 99%